The four agreements ebook A practical guide to personal freedom. - Ruiz, Don Miguel (Toltec Wisdom Book., 2011)
The incredible New York Times and international bestselling guide to true happiness. “This book by don Miguel Ruiz, simple yet so powerful, has made a tremendous difference in how I think and act in every encounter.”—Oprah Winfrey A bestseller for over a decade, published in fifty-three languages wordwide, The Four Agreements , bestselling author don Miguel Ruiz reveals the source of self-limiting beliefs that rob us of joy and create needless suffering. Based on ancient Toltec wisdom, The Four Agreements offer a powerful code of conduct that can rapidly transform our lives to a new experience of freedom, true happiness, and love. “Don Miguel Ruiz’s book is a roadmap to enlightenment and freedom.”—Deepak Chopra, Author, The Seven Spiritual Laws of Success “An inspiring book with many great lessons.”—Wayne Dyer, Author, Real Magic “In the tradition of Castaneda, Ruiz distills essential Toltec wisdom, expressing with clarity and impeccability what it means for men and women to live as peaceful warriors in the modern world.”—Dan Millman, Author, Way of the Peaceful Warrior